Geometry, kinetics and reactor network synthesis: Attainable limits for minimizing residence time in biomethane digesters. (8th May 2020) - Abunde Neba, F.; Tornyeviadzi, Hoese M.; Addo, Ahmad; Asiedu, Nana Y.; Morken, John; Østerhus, Stein W.; Seidu, Razak
Highlights: A new approach to optimize residence time using digester structure synthesis. Kinetic models are used to visualize digestion process as 3D geometric objects. The approach can simultaneously answer different design/optimization questions. Using digester structures minimize residence time compared to single digesters. The framework also extends performance targets of anaerobic treatment process. Abstract: This paper presents a theoretical framework to model anaerobic digester structures and define performance targets using regions of attainability constructed using kinetic models and fundamental processes: mixing and biodegradation. Two digestion cases, diary manure (case 1) and diary manure + lagoon inoculum (case 2) were considered and the following main findings were obtained. Case 1 presents a linear acidogenic and exponential methanogenic uncoupling, an optimized performance target of 216.45% with optimal digester structure consisting of CSTR (continuous stirred reactor) + PFR (plug flow reactor) run in parallel with a CSTR (6 days retention time, RT) or a CSTR with bypass from feed (2 days RT). Case 2 presents a linear methanogenic response, an optimized target of 142.47% with optimal digester structure consisting of a CSTR + PFR with bypass (2 & 6 days RT). The framework presented in this study can be used for simultaneous optimization of performance targets and digester networks.